Implementasi Teknologi Akuntansi di Era Digital: Peran Aplikasi Zahir Accounting - Fadila Ayu Utami; Agus Munandar (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to examine the use of the Zahir Accounting application in supporting the implementation of a more efficient and accurate accounting information system. Amid rapid technological developments, companies' need for digital accounting systems is increasing, especially in terms of financial reporting and transaction data management. Through a literature review and direct observation of the application's use, it was found that Zahir Accounting can accelerate the reporting process and minimize data entry errors. Additionally, the features offered are easy to understand, even for users without a strong accounting background. The results of the study revealed that the use of this software provides convenience through its superior automation features. With the help of this system, companies can compile financial reports more quickly and accurately. In addition, the accuracy of financial data is also more guaranteed, thereby helping management make more accurate and strategic decisions. Furthermore, the use of this application greatly helps in facilitating transaction tracking, managing inventory, and recording cash flow in a clearer and more transparent manner. The features offered are also quite easy to understand, even for users without a technical background. Its simple and intuitive interface makes the learning process faster. The implementation of Zahir Accounting has also proven to save time and minimize errors that often occur in manual processes. This, of course, has a positive impact on preparing neat, systematic, and easily accountable financial reports. To maximize the benefits of this application, it is important for companies to regularly evaluate its implementation.